2015
DOI: 10.3912/ojin.vol20no01man02
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Assessment and Nurses: What Does the Evidence Show?

Abstract: Suicide is at epidemic proportions both in the United States and across the globe. Yet, it is a preventable public health problem. Nurses practice on the front-lines and have the greatest number of opportunities to identify and intervene with suicidal patients. Most registered nurses (RNs) have little or no training in how to assess, evaluate, treat, or refer a suicidal patient. Because of this lack of training, RNs feel ill-prepared and afraid to talk to patients about suicide. The purpose of this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…Given that suicide is a leading cause of death in PWE, 5 identifying SI prior to progression is the first step in mitigating CS. This framework is based on an abundance of literature showing a strong association between SI and CS 12,13,23 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that suicide is a leading cause of death in PWE, 5 identifying SI prior to progression is the first step in mitigating CS. This framework is based on an abundance of literature showing a strong association between SI and CS 12,13,23 …”
Section: Discussionmentioning
confidence: 99%
“…SI has been established as a strong risk factor for death by suicide. Longitudinal studies within the general population have shown it to be a significant predictor for CS 12,13 . In the year prior to suicide, 83% of patients will see a health care provider at least once, and most persons (55%) will receive health care services in the 4 weeks prior to death by suicide 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, they are faced with ethical dilemmas (Valente, 2011; Valente & Saunders, 2004). Bolster et al (2015) studied the psychosocial barriers to managing suicide by oncology nurses. The nurses reported conflicts between their role in the prevention of suicide and in their commitment to patients at the end of their lives who asked to die with dignity.…”
Section: Representations Of Suicide In Care ­Professionalsmentioning
confidence: 99%
“…This conflict can be summarized as being between their moral values and what is required by their professional practices. Most studies report that nurses would like to feel more competent when dealing with someone contemplating suicide and that it would thus be a good idea to develop training programs (Bolster, Holliday, Oneal, & Shaw, 2015).…”
Section: Representations Of Suicide In Care Professionalsmentioning
confidence: 99%